Komitmen Organisasi, Disiplin Kerja Pada Kinerja Karyawan Unit Bandara Kelas Satu Mopah - Nurwijayanti Nurwijayanti; Aldisa Arifudin (Musamus Journal of Business & Management, 2020)
This research aims to determine the influence of organizational commitment and work discipline on the performance of civil servants in the corporate office of Mopah Merauke class I Airport. This type of research is a quantitative study based on empirical rational principles. This research Data was analyzed using multiple linear regression analyses using SPSS 23. The population in this study is all civil servants by taking a total sampling technique of 120 respondents. The results of hypothesized testing showed that simultaneously the organizational commitment and work discipline jointly had a positive and significant influence on employee performance. A partial organizational commitment has a positive and significant impact on employee performance, while working disciplines are positively but insignificant to employees ' performance at the Mopah Merauke class I Airport Operator's office. Keywords: Organizational Commitment, Work Discipline, Performance